Mira dentro de un tipi = Look inside a tepee - Schuh, Mari C., 1975- (Mankato, Minn. : Capstone Press, 2012)
"Simple text and photographs present tepees, their construction, and their interaction with the environment--in both English and Spanish"--Provided by publisher.
What is a tepee? -- Building a tepee -- Inside a tepee -- Tepees today.
Includes index.
Keywords: Tipis -- Juvenile literature